2021
DOI: 10.21775/cimb.041.063
|View full text |Cite
|
Sign up to set email alerts
|

Entry of Alphaherpesviruses

Abstract: Alphaherpesviruses are enveloped viruses that enter cells by fusing the viral membrane with a host cell membrane, either within an endocytic vesicle or at the plasma membrane. This entry event is mediated by a set of essential entry glycoproteins, including glycoprotein D (gD), gHgL, and gB. gHgL and gB are conserved among herpesviruses, but gD is unique to the alphaherpesviruses and is not encoded by all alphaherpesviruses. gD is a receptor-binding protein, the heterodimer gHgL serves as a fusion regulator, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 254 publications
(284 reference statements)
1
7
0
Order By: Relevance
“…7A ). This suggests that the fusion mechanism is the same regardless of the receptor, which is consistent with the current model [reviewed in (10, 14, 15)]. Therefore, we hypothesize that the differences in fusion extent in the presence of HVEM200t-His 8 or nectin345t-His 8 are due to differences in fusion efficiency.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…7A ). This suggests that the fusion mechanism is the same regardless of the receptor, which is consistent with the current model [reviewed in (10, 14, 15)]. Therefore, we hypothesize that the differences in fusion extent in the presence of HVEM200t-His 8 or nectin345t-His 8 are due to differences in fusion efficiency.…”
Section: Resultssupporting
confidence: 89%
“…In HSV-1, entry-associated functions are distributed across four viral glycoproteins: gD, gH, gL, and gB [reviewed in (1012)]. According to the current model, these four viral glycoproteins orchestrate membrane fusion through a sequential activation process termed regulatory cascade (13) [reviewed in (10, 14, 15)]. First, the receptor-binding glycoprotein, gD, binds one of its three cognate receptors on the surface of the host cell and undergoes a conformational change, enabling it to bind and activate the gH/gL complex.…”
Section: Introductionmentioning
confidence: 99%
“…We concluded that the gH-S830N mutation contributed to enhanced entry using the same reasoning as for the gH-H789Y mutation above. gH-S830 maps to the short gH CT (residues 825–838) that is essential for WT levels of fusion ( 1 , 2 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Human nectin-1 shares 96% amino acid identity with porcine nectin-1. Although PrV gD exhibits similar affinity for both human and porcine nectin-1 [ 26 , 28 , 29 ], the PrV gD binding affinity for human nectin-1 is ten-fold higher than that of HSV-1 gD [ 26 , 27 ], which may explain human PrV infection. Despite the low amino acid homology of PrV and HSV gDs, most of their secondary structure elements are similar.…”
Section: Prv Invasionmentioning
confidence: 99%